Desiccation tolerance, development maturation and storage of seeds of several tropical tree species - Lima Junior, Manuel de Jesus Vieira (Inglaterra, 2025)
Desiccation tolerance of mature seeds of Ceiba pentandra, Cedrela odorata, Dalbergia spruceana, Parkia igneiflora, Schizolobium amazonicum and Tabebuia alba was investigated. Seeds of all species tolerated desiccation to low moisture content (around 10% to 15% equilibrium relative humidity). Five different post harvest drying treatment to immature seeds of C odorata were imposed. In all treatments, ability to germinate after desiccation to 10% moisture content was no less than that of undried seeds extracted form fruits soon after collection. However, survival was affected by further desiccation to 3% moisture content. Seed longevity in air-dry storage was increased b some drying treatments. Drying in a thin layer for 10 to 20 days was the best treatment to improve desiccation tolerance and subsequent longevity. changes in hability of C pentandra seeds to survive desiccation and germinate, in subsequent seedling establishment and in the attainment of maximum potential longevity (Ki) were investigated during seed development and maturation. The onset of desiccation tolerance to 4% moisture content was abrupt and coincided with the onset of germinability, i.e. 5 days after mass maturity, and remained unchanged until the end of the shedding period. A similar pattern was observed for mean seedling dry weight. Maximum potential longevity was attained 19 days after mass maturity. Seed quality did not decline afterwards. Slow post-harvest drying was beneficial only for seeds which had achieved mass maturity. The viability equaton could be applied fro C. pentandra, C. odorata, T. alba and Dalbergia spruceana. Seeds of C. pentandra, S. parahyba var amazonicum, p. igneiflora and T. alba could also survive when sored dry at sub-zero temperature. C. pentandra, C. odorata and T. alba can thus be definitely classified as species with orthodox seed storage behaviour, while D. spruceana, S amazonicum and P. igneiflora are most likely to also show orthodox seed storage behaviour.